2020
DOI: 10.1152/ajpendo.00163.2020
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control of type 2 diabetic patients with coronavirus disease during hospitalization: a proposal for early insulin therapy

Abstract: TO THE EDITOR: The world is watching the progress of coronavirus disease (COVID᎑19) pandemic. Older age and pre-existing medical conditions, specifically diabetes mellitus, hypertension, ischemic heart disease, and chronic lung disease, are associated with a more severe course of . Diabetes mellitus is one of the most prevalent comorbidities among patients hospitalized due to . Data obtained from 21 hospitals in Wuhan, China, showed that 25% of the reported COVID-19 fatalities had a history of diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, in contrast to the implication that the androgen dependence of COVID-17 severity may offer a strategy for using counter-measures to protect against COVID-19 ( 161 ), the metabolic effect needs more careful consideration. The management of metabolic control in critically ill patients is much more challenging than in those not acutely ill and many of the normal drugs used in diabetes are counter-indicated, with insulin being the most appropriate therapy ( 162 ). In addition, there are good reasons why glucocorticoids, which may seem counter-indicated, may actually be very beneficial in critically ill patients ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the implication that the androgen dependence of COVID-17 severity may offer a strategy for using counter-measures to protect against COVID-19 ( 161 ), the metabolic effect needs more careful consideration. The management of metabolic control in critically ill patients is much more challenging than in those not acutely ill and many of the normal drugs used in diabetes are counter-indicated, with insulin being the most appropriate therapy ( 162 ). In addition, there are good reasons why glucocorticoids, which may seem counter-indicated, may actually be very beneficial in critically ill patients ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of diabetics in India was 31.7 million in the year 2002, and it is estimated that the number of diabetics in 2030 will be 79.4 million in India (Khatib et al, 2008). In hospitalized patients with COVID 19, DM is the most prevalence co-morbidity (Nakhleh and Shehadeh, 2020). In this review, we discuss the conjectural role of angiotensin-converting enzyme II (ACE2) with type 2 DM and COVID 19.…”
Section: Introductionmentioning
confidence: 99%
“…Nakhleh and Shehadeh have argued that patients with type 2 diabetes and COVID-19 requiring hospitalization should have early insulin therapy. 6 They suggested that this approach could control hyperglycemia and, in turn, have positive immunomodulatory effects. The complex interactions among ACE 2 cellular receptors and their varying levels in different tissues, circulating ACE 2 released from cellular membranes, angiotensin II, angiotensin 1-7, and SARS-CoV-2 potentially contribute to both viral infection and associated tissue injury and to host defenses.…”
mentioning
confidence: 99%